Fundamentals of Fibre-Reinforced Soil Engineering - Shukla, Sanjay Kumar (Developments in Geotechnical Engineering, 2017)
This book is intended to serve as a one-stop reference on fibre-reinforced soils. Over the past 30-35 years, the engineering behaviour of randomly distributed/oriented fibre-reinforced soil, also called simply fibre-reinforced soil, has been investigated in detail by researchers and engineers worldwide. Waste fibres (plastic waste fibres, old tyre fibres, etc.) create disposal and environmental problems. Utilization of such fibres in construction can help resolve these concerns. Research studies and some field applications have shown that the fibres can be utilized in large quantities in geotechnical and civil engineering applications in a cost-effective and environmentally friendly manner. This book covers a complete description of fibres, their effects when included within a soil or other similar materials such as the fly ash, and their field applications. It gives a detailed view of fibre-reinforced soil engineering. The book will be useful to students, professional, and researchersalike, and can also serve as a text for graduate coursework and professional development programs.